2019
DOI: 10.35437/intnur.issn.2663-4481.2019.01.02.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Simulation-Based Learning Using Virtual Reality in Nursing Student: A Meta-Analysis

Abstract: Purpose: This study is a meta-analysis to assess the effect of simulation-based learning using virtual reality (VR) on knowledge, affective, and performance domain outcomes of learning in nursing students. Results:A total of 10 studies (5 randomized control trials (RCTs) and 5 non-RCTs) involved 630 nursing students. As a whole, simulation-based learning using VR appeared to have beneficial effects on the knowledge (I 2 =50%, 95% CI 0.35 [0.09, 0.62], P=0.009), have no significant difference on the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 17 publications
0
10
1
1
Order By: Relevance
“…This meta-analysis demonstrated that VR simulation significantly increased skill performance among nursing students. These findings contradict those of other meta-analyses and systematic reviews in VR simulation 7,10,27 . In the meta-analysis by Chen et al, 10 all the included studies used simulation-based nursing education methods, including mannequin-based simulation and plastic models in the control groups.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…This meta-analysis demonstrated that VR simulation significantly increased skill performance among nursing students. These findings contradict those of other meta-analyses and systematic reviews in VR simulation 7,10,27 . In the meta-analysis by Chen et al, 10 all the included studies used simulation-based nursing education methods, including mannequin-based simulation and plastic models in the control groups.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, the meta-analysis by Chen et al 10 reported no increase in self-confidence after VR simulation. In another meta-analysis conducted by Zhang et al, 27 VR simulation appeared to impact self-confidence negatively. These findings may result from the characteristics of self-efficacy and self-confidence and the methodological differences in the intervention's type, time, duration, and repeatability.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Aktuelle Übersichtsarbeiten zeigen, dass es sich bei den in der Pflegebildung verwendeten VR überwiegend um Trainingsumgebungen handelt, in denen klinische Szenarien (Arbeitsprozesse oder Handlungen) simuliert werden (Liaw et al 2018, Weiß et al 2018, Bracq et al 2018, Fealy et al 2019, Kyaw et al 2019, Zhang et al 2019, Foronda et al 2020, Rourke et al 2020, Chen et al 2020, Coyne et al 2021…”
Section: Vr-anwendungen In Der Pflegebildungunclassified